THE IMPORTANCE OF THE AUDITORY ANALYZER IN THE FORMATION OF PHONEMATIC PERCEPTION - Kuchkarova, Gulnoza Kurbonboy qizi (THE INNOVATION ECONOMY, 2026)
The auditory system is a set of mechanical receptors and nervous structures that sense and analyze sound vibrations through the auditory organs. The structure of auditory analyzers, especially its peripheral part, differs in humans and animals. In higher vertebrates, including most mammals, auditory analyzers consist of the outer, middle, and inner ear, as well as the auditory nerve and nerve centers connected in series. The development of the auditory analyzers central unit is related to environmental factors and the importance of auditory analyzers in animal behavior. The shell barrier is of primary importance in detecting sound vibrations. This barrier consists of filtering auditory receptors located in a row along the cochlear barrier, which perform a mechanical spectral analysis of sound. Receptors receive vibrations in the range of 0.1 to 10 nm. Neurons located in the central part of auditory analyzers are sensitive to certain sound vibrations. Neural elements of auditory analyzers are sensitive to sound vibrations, as well as sound strength, duration, etc. The neurons of the central nervous system, and especially its upper part, are sensitive to complex features of sound (eg, frequency, direction and movement of sound amplitude modulation).